The space between: Mix taping as a ritual of distance. (2nd July 2016) - Drew, Rob
ABSTRACT: As an affectively charged medium of communication, the mix tape embodies a registry of human longings. In their accounts of exchanging mixes and their reflections on the meanings attached to them, mixers display the gamut of hopes and fears surrounding their relationships. While the mix tape often is represented as a token of unreserved intimacy, the practice of making and exchanging mixes can as easily be understood as a ritual of distance, one that betrays our ambivalence about dialogue and our delight in one-way communication. Based on interviews with donors and recipients of mix tapes and CDs, I will summarize four versions of the mix as a ritual of distance—communion, devotion, display, and fantasy—each building on its predecessor to round out the mix's relational meaning.